Imagining an Islamic Japan: pan-Asianism's encounter with Muslim mission. Issue 2 (2nd April 2020) - Brandenburg, Ulrich
Abstract: Under the influence of a globalized discourse about Japan's uncertain religious future, many Muslims in the early twentieth century placed Meiji Japan in a religious imaginary, in which Japan became the arena for a competition between different religious aspirations. This religious imaginary is an example of the effect of mediated connections, in which information from Japan to Muslim majority regions and vice versa was generally transmitted through Euro-American channels. As a result, Muslims envisioned strategies to convert the Japanese to Islam, aiming to demonstrate the universal relevance of their religion. While this led to a number of missionary endeavours, which quickly ended in failure, it was in the realm of the imperial imaginary that Islam as a geopolitical tool became attractive to pan-Asianist circles in Japan. In collaboration with select Muslim partners and by giving visibility to the existence of Islam in Japan, Japanese pan-Asianists of the late Meiji period tried to inspire loyalties in Muslim regions for the benefit of Japan's imperial goals. Although this partnership would not last long, it prepared the ground for Japan's Islam policy in the 1930s and 1940s, which characteristically blended pan-Asianism with religion and the showcasing of Muslim life in Japan.